Risks, incidents, guidelines, and strategies pertaining to chemical storage and handling in primary healthcare – a narrative review - Hanis Abdul Rani; Aniza Ismail; Hasni Mohd Jaafar; Norfazilah Ahmad; Nor Aliya Ayub (Universiti Kebangsaan Malaysia, 2025)
Effective chemical storage and handling are critical in primary healthcare (PHC) to safeguard healthcare workers, patients, and the environment. Despite their importance, PHC facilities face unique challenges due to limited resources, inadequate monitoring, and the absence of tailored guidelines and protocols. This narrative review explores the state of chemical storage and handling practices in PHC. A systematic methodology guided this narrative review, including a comprehensive literature search using PubMed, Scopus and Web of Science with defined inclusion and exclusion criteria. Given the scarcity of PHC-specific studies, a purposive selection approach was employed to incorporate evidence from broader healthcare contexts. Data extraction and thematic analysis identified key risks, documented incidents, and evidence-based strategies for improving chemical storage and handling. Findings reveal that improper chemical practices lead to acute health effects such as respiratory distress and chemical burns, chronic conditions like asthma and operational disruptions. Non-compliance with regulations exacerbates financial and reputational risks. Case studies, including an ammonia gas leak in Malaysia and chlorine gas exposure in the United Kingdom, highlight the severe consequences of inadequate practices. Six strategies to improve chemical storage and handling in PHC settings were identified: i) regular monitoring and risk assessments, ii) safe physical storage practices, iii) training and education, iv) use of personal protective equipment (PPE), v) incident management and response plans, and vi) inventory organization and storage efficiency. These evidence-based strategies can mitigate risks and enhance safety. The review underscores the urgent need for PHC-specific guidelines and future research to address existing gaps and foster safer PHC environments.